Catalytic combustion of hydrogen and methane for autothermal reformer start-up ignition system - Razak, M. M. A.; Mustafa, A.; Nasri, N. S.; Songip, A.R (2004)

(untitled)
Catalytic combustion is a phenomenon in which fuel and oxidant are completely oxidized on a catalytic surface. The interest in this process arises for two reasons: for pollution abatement and for energy generation. The objective of this research is to study the amount of heat produced from catalytic combustion system by adopting a bi-fuel concept: hydrogen and methanc. The combustion of hydrogen is used to pre-heat the reactor to reach the ignition temperature of methane. The light off temperature of methane with airICH4 ratio of 5.3 is 368 0 C. Platinum has been found as one of the catalyst that ignites hydrogen at room temperature. Oncc thc ignition of mcthane is achieved. thc flow of liydrogcn is discontinued and replaced by methanc.